THE DEFECT REDUCTION IN WIRE PARTS PROCESS FOR CAR SEAT - Thavornwat, Chalermsak; Kanchana, Rapee; Jarupinyo, Srirai; Wattanajitsiri, Voraya (Thai Industrial Engineering Network Journal, 2017)
This research aimed to reduce a number of defects in wire forming process of car seat production so as to achieve the company’s target at least 20% decrease. From initial study during January to March 2014, it found that at CNC section had the average maximum number of defects with 720.7 kg. Therefore CNC was selected for improvement in this study. During April 2014, data was collected in three processes; wire straightness, wire setup and wire processing, it found the number of defects were 252.1 kg, 134.6 kg, and 72 kg, respectively. The research methodology began with prioritizing the problem by Pareto diagram, then using cause and effect diagram to investigate the causes of the problem and finding the root cause of each problem by why-why analysis. Furthermore, many IE techniques such as design and fabricating inspection tool, visual control were applied to improve work method as well as the linear regression analysis was also used to investigate the relationship among variables. After improvement by fabricating wire straightness checking tool, establishing a standard operation procedure, identifying tolerance standard and spring back value in different physical properties and filing its program properly, the result showed that a total number of defects at both wire straightness and wire setup processes reduced from 386.7 kg. to 219.9 kg, as of 43.13% improvement.